Kepemimpinan Kepala Sekolah dalam Membina Motivasi Pendidik Anak Usia Dini: Principal Leadership in Fostering Motivation of Early Childhood Educators - Sabariah, Sabariah; Atiqoh, Atiqoh; Gunawan, Wawan; Rahmi, Agustina; Danu, Retno (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to investigate the leadership of school principals in fostering motivation among educators in the Nur Masithah Sampang Playgroup. The research method employed is descriptive qualitative, utilizing data collection techniques through observation, interviews, and documentation. Data were analyzed through reduction, presentation, and conclusion. The findings indicate that school principals motivate teachers through meetings to enhance self-confidence and positive attitudes towards young children. They also empower teachers by organizing competitions to develop children's motor skills, exemplifying discipline, and providing training. Fair treatment and encouragement to work with enthusiasm are highlighted as effective leadership strategies. Supporting factors include quality human resources, good teacher performance, and a supportive environment. Meanwhile, diverse personal characteristics, an unsupportive environment, and a lack of learning facilities are inhibiting factors in leadership efforts.